Spectroscopic studies of the intermolecular interactions of Congo red and tinopal CBS with modified cellulose fibers - Yamaki, Sahori B (Langmuir : the ACS journal of surfaces and colloids, 2005)
The adsorption of Congo red and tinopal CBS dyes on cellulose fibers was investigated using electronic absorption and fluorescence spectroscopies. Hydrogen bonds appear to be relevant for the dye-fiber interactions as indicated by the solvatochromism of Congo red in water, methanol, and dimethyl sulfoxide solutions, and when adsorbed on cellulose fibers. We also demonstrate that electrostatic interactions play an important role in the dye-medium interaction, through the analysis of absorption spectra of Congo red and fluorescence spectra of tinopal in aqueous solutions containing salt and in layer-by-layer nanostructured films with poly(allylamine hydrochloride). For instance, dye adsorption was enhanced when salt was added to the dipping solution, which was explained by the synergistic effect between the conformational changes of the cellulose and changes in the solvation layer around the cellulose chains and around dye molecules. On the basis of the fluorescence results for tinopal CBS, we inferred that dye aggregation is not relevant for adsorption on the fibers. In addition, fluorescence spectroscopy is proven very sensitive for studying the organization of dye molecules in layer-by-layer films, particularly those undergoing irreversible structural changes